Pengembangan Potensi Desa Dengan E-commerce Desa Sumberejo Kapanewon Semin Kabupaten Gunungkidul - Pranata, Adrianus Yoga (Jurnal Atma Inovasia, 2023)
Community Service Activities carried out in areas that have been determined through Real Work Lectures. KKN 81 UAJY is carried out by conducting KKN activities directly in the designated area. Group 35 obtained a resettlement location in Sumberejo Village, Semin District, Gunungkidul Regency, Special Region of Yogyakarta. The work program that will be carried out by the group is village potential and tourism pocketbooks in Mangunan village. The potential work program in Sumberejo Village is to provide information about developing village potential. Pocket book work program in Sumberejo village by utilizing E-commerce from the Tokopedia and Shopee applications. It is hoped that the work program compiled by the group can help the community's economy.